EDUKASI KONSEP BERMAIN PADA ANAK GUNA MENINGKATKAN TUMBUH KEMBANG ANAK DI TK KRISTEN STABELAN BANJARSARI SURAKARTA - TOTOK WAHYUDI; Marni; Ikrima Rahmasari; Putri Nirmala Kusumaningrum (Universitas Veteran Bangun Nusantara, 2024)
The community service program aims to improve the understanding of teachers and guardians or parents regarding monitoring growth and development and the concept of play to improve and support the growth and development process in children. By providing education on the concept of play in supporting growth and development in children, it is hoped that the child's growth and development will be good and in accordance with the child's age level. This is also a form of prevention of growth and development disorders in children. The community service team conducted a survey and continued with submitting a permit letter to the Kindergarten and providing invitations to teachers and guardians of children. The activity was continued by providing education which ended with an evaluation of the community service activities. Assistance was carried out by the community service team in play therapy given to children who were divided into 4 groups. The children were very enthusiastic in participating in the activity with various types of games in the form of puzzles, coloring paper with colored sand. The results of this community service show an increase in understanding from teachers and parents or guardians regarding growth and development and the types of games that can support the growth and development process in children. This is supported by a positive response from parents' answers and the enthusiasm of teachers and parents or guardians in participating in the service event until the end.